2017
DOI: 10.1590/0001-3765201720160784
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the silverside Atherinella brasiliensis in a subtropical estuary with some insights concerning the weight-length relationship

Abstract: Specimens of Brazilian silverside (Atherinella brasiliensis,We present some considerations with regard to the general methodology for adjusting weight-length relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 23 publications
3
17
2
Order By: Relevance
“…Individual growth rates in fish populations are highly dependent on food availability (Billerbeck et al ., 2001). Several studies have shown that A. brasiliensis changes its prey categories throughout multiple sites in estuaries (Alves et al ., 2016; Carvalho et al ., 2017; Carvalho & Spach, 2015; Contente et al ., 2010b), and this pattern appears to be associated with ecophysiological factors, as described by Cottingham et al . (2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individual growth rates in fish populations are highly dependent on food availability (Billerbeck et al ., 2001). Several studies have shown that A. brasiliensis changes its prey categories throughout multiple sites in estuaries (Alves et al ., 2016; Carvalho et al ., 2017; Carvalho & Spach, 2015; Contente et al ., 2010b), and this pattern appears to be associated with ecophysiological factors, as described by Cottingham et al . (2018).…”
Section: Discussionmentioning
confidence: 99%
“…To assess the ontogenetic variation in condition indicator of the Brazilian silverside sizes from both estuaries, we used a relative condition factor (Kn) (Carvalho et al ., 2017). The b value from the weight–length relationship was used to calculate the condition factor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with the findings of Alves et al (2016) in this estuary. Three characteristics of A. brasiliensis were identified as factors important to its success in estuarine areas: salinity tolerance (Souza-Bastos, Freire, 2011), slow rates of growing with positive alometric coeficients and short-lived life cycle (Contente et al, 2011;Carvalho et al, 2017). Furthermore, in accordance with the findings of other authors, the Brazilian silverside showed higher abundance in habitats less affected by the hydrodynamic process, such as extensive sand (Pessanha, Araujo, 2001) and mud flats (Campos et al, 2015), and also in sites which provide more availability of habitats, as such tidal creeks and mangroves (Neves et al, 2006;Fávaro et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…where TW is the predicted total weight, TL the total length, a the coefficient of proportionality, and b the allometric coefficient (Carvalho et al 2017, Possamai et al 2018. A paired t-test was performed to compare length-weight relationship parameters between sex by sampled location.…”
Section: Statistical Analysesmentioning
confidence: 99%